2013
DOI: 10.1063/1.4818513
|View full text |Cite
|
Sign up to set email alerts
|

An improved model for nanosecond pulsed laser ablation of metals

Abstract: A model is presented for the ablation of metals by nanosecond laser pulses, based on one-dimensional heat flow with temperature dependent material properties. A numerical optical calculation is introduced to account for laser beam absorption in the target, utilizing established matrix methods for electromagnetic plane wave propagation in multi-layered media. By including the effects of reflection from the dielectric-metal interface, the fall in reflectivity of aluminum during nanosecond laser pulses above the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
42
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 32 publications
0
42
0
1
Order By: Relevance
“…The behavior of this kind of grating has been already analyzed in previous works [9,10]. On the other hand, rotary encoders with the grating engraved by laser ablation [11,12] on the external curved side of a steel cylinder have recently been developed [13][14][15]. It has been demonstrated that gratings engraved by nanosecond laser ablation on steel substrates act like amplitude gratings due to their surficial roughness [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The behavior of this kind of grating has been already analyzed in previous works [9,10]. On the other hand, rotary encoders with the grating engraved by laser ablation [11,12] on the external curved side of a steel cylinder have recently been developed [13][14][15]. It has been demonstrated that gratings engraved by nanosecond laser ablation on steel substrates act like amplitude gratings due to their surficial roughness [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…It corresponds to the same parameters as figure 2, but takes into consideration polychromatic light with Δλ = 50 nm and lateral size μ = a 10 m. For completeness, other particular cases corresponding to finite monochromatic sources and punctual polychromatic sources are analyzed and shown in the appendix. They are obtained from equation (12). These cases are of interest in other configurations of optical rotary encoders.…”
mentioning
confidence: 99%
“…It has been shown that the absorption of a significant fraction of the laser energy by the plasma that is created above the surface is an important phenomenon during nanosecond laser ablation [34], [35]. Including plasma absorption can lead to significant improvement of model predictions [36,37,38,39]. In this context, using the method developed for graphite ablation by Bulgakova et al [40], the plasma absorption is estimated using the total optical thickness of the ablation plume Λ such that…”
Section: Introductionmentioning
confidence: 99%
“…In order to understand and further improve the process parameters, different modelling approaches have been developed either analytically [5][6][7][8][9][10][11][12][13][14][15], or numerically [13,[16][17][18][19][20][21]. Conventional numerical modelling methods such as finite elements (FE), finite difference (FD) and finite volume (FV) may not be able to predict complex processes when multiple materials and phases are interacting due to the connected mesh that describes the computational domain.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the fact that all the elements in the mesh are connected to each other and cannot leave the mesh, the splashed particles in laser cutting, drilling and ablation cannot be observed in such methods. Some authors [21][22][23] simulated the protrusion formed by the laser ablation/machining by deleting the elements that have their temperatures greater than the boiling temperature. However, such approach fails to provide information on the behaviour of ejected material.…”
Section: Introductionmentioning
confidence: 99%